The Merciful and Compassionate God: Biblical Theology in an Islamic Context - Botros, Emad (My University, 2013)
﻿The primary purpose of this study is to write a biblical theology in the form of commentary in an Islamic context. This study argues that since the Old Testament is Christian authoritative Scripture, its theological message must be a fundamental resource for writing a biblical theology in an Islamic context. This study uses the narrative of Exod 32-34 as an example of the rich contribution the theological message of narratives makes to biblical theology. The theological message of this narrative reveals powerfully the character of the biblical God in dealing with the crisis of worshiping the golden calf in an Islamic context. This study calls for a move from an apologetic defensive theology that merely requires answering explicit challenges that Islam has posed to Christianity through the centuries to a biblical theology that addresses the hermeneutical questions that arise from the rhetorical Islamic context.
Keywords: biblical, theology, Islamic, context, God, Christianity